2023
DOI: 10.3390/jof9040452
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis Exacerbates Inflammation and Mucus Hypersecretion in a Murine, Elastase-Induced-COPD Model

Abstract: Inflammation and mucus hypersecretion are frequent pathology features of chronic respiratory diseases such as asthma and COPD. Selected bacteria, viruses and fungi may synergize as co-factors in aggravating disease by activating pathways that are able to induce airway pathology. Pneumocystis infection induces inflammation and mucus hypersecretion in immune competent and compromised humans and animals. This fungus is a frequent colonizer in patients with COPD. Therefore, it becomes essential to identify whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
4
5
0
Order By: Relevance
“…In this work, we showed that the presence of inflammation cuffs in the lungs showed results comparable to the previously described [35]. Interestingly, the number of cuffs between animal groups infected (Pc) and COPD infected (ELT-Pc) did not show a significant difference, indicating that not only must the number of cuffs be evaluated, but the size and the cell components of each cuff must to be coherent with the analysis of cytokines previously presented [35]. Another result of this work is the increment of IL1β mRNA levels indicating the activation of the pathway.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this work, we showed that the presence of inflammation cuffs in the lungs showed results comparable to the previously described [35]. Interestingly, the number of cuffs between animal groups infected (Pc) and COPD infected (ELT-Pc) did not show a significant difference, indicating that not only must the number of cuffs be evaluated, but the size and the cell components of each cuff must to be coherent with the analysis of cytokines previously presented [35]. Another result of this work is the increment of IL1β mRNA levels indicating the activation of the pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Given the induction of the IL1β pathway in this animal model, and recognizing the association between this pathway and mucus secretion, we initially examined the presence of a cAMP response element (CRE) in promoters of Muc5ac and Muc5b. These mucin genes showed a clear increment in their expressions during the development of COPD induced by elastase and synergically incremented by the presence of Pneumocystis in the previous work [ 35 ]. A CRE sequence was only detected in the promoter of Muc5b ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations